George Santayana's Marginalia, A Critical Selection : Book Two, McCord-Zeller - Santayana, George, 1863-1952 (Book collections on Project MUSE., 2011)
A selection of Santayana's notes in the margins of other authors' works that sheds light on his thought, art, and life. In his essay "Imagination," George Santayana writes, "There are books in which the footnotes, or the comments scrawled by some reader's hand in the margins, may be more interesting than the text." Santayana himself was an inveterate maker of notes in the margins of his books, writing (although neatly, never scrawling) comments that illuminate, contest, or interestingly expand the author's thought. These volumes offer a selection of Santayana's marginalia, transcribed from books in his personal library. These notes give the reader an unusual perspective on Santayana's life and work. He is by turns critical (often), approving (seldom), literary slangy, frivolous, and even spiteful. The notes show his humor, his occasional outcry at a writer's folly, his concern for the niceties of English prose and the placing of Greek accent marks. These two volumes list alphabetically by author all the books extant that belonged to Santayana, reproducing a selection of his annotations intended to be of use to the reader or student of Santayana's thought, his art, and his life. Santayana, often living in solitude, spent a great deal of his time talking to, and talking back to, a wonderful miscellany of writers, from Spinoza to Kant to J.S. Mill to Bertrand Russell. These notes document those conversations.